2015
DOI: 10.1118/1.4915492
|View full text |Cite
|
Sign up to set email alerts
|

Dose ratio proton radiography using the proximal side of the Bragg peak

Abstract: Purpose: In recent years, there has been a movement toward single-detector proton radiography, due to its potential ease of implementation within the clinical environment. One such single-detector technique is the dose ratio method in which the dose maps from two pristine Bragg peaks are recorded beyond the patient. To date, this has only been investigated on the distal side of the lower energy Bragg peak, due to the sharp falloff. The authors investigate the limits and applicability of the dose ratio method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…An alternative approach is to use a single distal detector beyond the patient, in a similar fashion to portal imaging devices in radiotherapy. A variety of approaches have been tested (Martišíková et al 2013, Rinaldi et al 2014, Telsemeyer et al 2012b, 2014, Doolan et al 2015a, but in this work we investigate an extension to the time-resolved method. This approach relies on the use of a proton beam whose range is modulated by a rotating range modulator (RM) wheel, which in turn generates a time-varying dose at the detector (Lu 2008, Gottschalk et al 2011, Testa et al 2013.…”
Section: Single-detector Proton Radiographymentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach is to use a single distal detector beyond the patient, in a similar fashion to portal imaging devices in radiotherapy. A variety of approaches have been tested (Martišíková et al 2013, Rinaldi et al 2014, Telsemeyer et al 2012b, 2014, Doolan et al 2015a, but in this work we investigate an extension to the time-resolved method. This approach relies on the use of a proton beam whose range is modulated by a rotating range modulator (RM) wheel, which in turn generates a time-varying dose at the detector (Lu 2008, Gottschalk et al 2011, Testa et al 2013.…”
Section: Single-detector Proton Radiographymentioning
confidence: 99%
“…As well as providing structural information not otherwise visible in the WET map, these images provide information about which WET values are reliable. Many works have argued the importance of the WET map for proton treatments and quality assurance (Schneider and Pedroni 1995, Telsemeyer et al 2012a, Doolan et al 2015a and the higher order images provide confidence on which WET values can be trusted and which are potentially subject to range mixing. In this work we have shown that it is possible to use the higher order images to create a mask of unreliable pixels that can be subsequently applied to the WET map.…”
Section: Higher Order Images To Determine Wet Reliabilitymentioning
confidence: 99%
“…Range uncertainties appear to be a major reason that prevents proton therapy reaching its maximum potential in sparing healthy tissue [3] . A number of different approaches to mitigate the effects (robust treatment planning [5] ) or to reduce range uncertainties (proton radiography [6] , proton computed tomography (pCT) [7] , dual energy CT (DECT) [8] ) are being investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Integrating systems measure the integrated signal of the particles downstream of the object being imaged (pRad: 14,15 ; iRad: 16 ; pCT: 17 ; iCT: 16,[18][19][20]. Most of these works focus on the usage of carbon ions due to the less pronounced MCS, which is especially important for nontracking systems.…”
Section: Introductionmentioning
confidence: 99%